A4NH 2020 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
Resilient food systems. Zoonoses transmission. Food safety in fresh-food markets. As the COVID-19 pandemic swept across the globe, phrases that had most often been found in research papers suddenly emerged on the front pages of newspapers and in trending topics on social media. Countries, corporations, and consumers alike struggled to understand not only how to cope with the threat of the disease itself, but also with meeting basic needs, such as food security, nutrition, and health, as lockdowns and mobility restrictions reshaped the world in very unequal ways, seemingly overnight.